2019
DOI: 10.1002/celc.201900168
|View full text |Cite
|
Sign up to set email alerts
|

Spray‐Flame‐Synthesized LaCo1−xFexO3 Perovskite Nanoparticles as Electrocatalysts for Water and Ethanol Oxidation

Abstract: Coupling electrochemical generation of hydrogen with the concomitant formation of an industrially valuable product at the anode instead of oxygen can balance the high costs usually associated with water electrolysis. We report the synthesis of a variety of nanoparticulate LaCo1−xFexO3 perovskite materials through a specifically optimized spray‐flame nanoparticle synthesis method, using different ratios of La, Co, and Fe precursor compounds. Structural characterization of the resulting materials by XRD, TEM, FT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
24
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 30 publications
(26 citation statements)
references
References 62 publications
1
24
0
Order By: Relevance
“…For oxide nanoparticles prepared by spray‐flame synthesis, the calculation of an average particle size based on the assumption of spherical particles is well justified . Accordingly, average particle sizes of the perovskites between 7 and 13 nm can be estimated, which agree well with our previously reported particle size distributions determined by TEM . The XRD patterns of the synthesized perovskites (Figure ) indicate the presence of a dominant perovskite phase with a minor content of La 2 O 3 .…”
Section: Resultssupporting
confidence: 84%
“…For oxide nanoparticles prepared by spray‐flame synthesis, the calculation of an average particle size based on the assumption of spherical particles is well justified . Accordingly, average particle sizes of the perovskites between 7 and 13 nm can be estimated, which agree well with our previously reported particle size distributions determined by TEM . The XRD patterns of the synthesized perovskites (Figure ) indicate the presence of a dominant perovskite phase with a minor content of La 2 O 3 .…”
Section: Resultssupporting
confidence: 84%
“…For LaFe 1‐x Co x O 3 materials, La enrichment on the surface was reported, [38b] as well as on LaFeO 3 [41] . However, STEM‐EDX measurements indicated an A‐cation enrichment as well on the surface [3a] . In contrast, B‐cation enrichment is reported for La 1−x Sr x NiO 3 after thermal decomposition of amorphous citrate materials [42] .…”
Section: Resultsmentioning
confidence: 99%
“…The data showed that higher Fe substitution had a lower catalytic activity (ethanol oxidation), while lower Fe substitution offered higher electrocatalytic performance. 97 In another report, cinnamyl alcohol oxidation kinetics with tertiary butyl hydroperoxide (TBHP) over the same LaCo 1– x Fe x O 3 perovskites showed beneficial effects of trivalent Fe in the perovskites. The reaction between liquid-organic moieties was catalyzed heterogeneously by the perovskite produced reactive oxygen species for surface kinetic reaction.…”
Section: Particles For Catalytic Applicationmentioning
confidence: 99%